2021
DOI: 10.1101/2021.12.16.472997
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dopamine and GPCR-mediated modulation of DN1 clock neurons gates the circadian timing of sleep

Abstract: The metronome-like circadian regulation of sleep timing must still adapt to an uncertain environment. Recent studies in Drosophila indicate that neuromodulation not only plays a key role in clock neuron synchronization but also affects interactions between the clock network and brain sleep centers. We show here that the targets of neuromodulators, G-Protein Coupled Receptors (GPCRs), are highly enriched in the fly brain circadian clock network. Single cell sequencing indicates that they are not only differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 61 publications
1
8
0
Order By: Relevance
“…We were surprised to discover that cell surface protein transcripts, including GPCRs and CSMs, are the best definers of neuron identify, for DANs as well as for clock neurons. We had previously found that GPCRs can identify clock neurons (Schlichting et al, 2021), and these data extend this conclusion to many other classes of cell surface proteins as well as to DANs. CSMs are critical for nervous system wiring during development, best illustrated perhaps by their remarkably complex expression patterns during fly visual system development.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…We were surprised to discover that cell surface protein transcripts, including GPCRs and CSMs, are the best definers of neuron identify, for DANs as well as for clock neurons. We had previously found that GPCRs can identify clock neurons (Schlichting et al, 2021), and these data extend this conclusion to many other classes of cell surface proteins as well as to DANs. CSMs are critical for nervous system wiring during development, best illustrated perhaps by their remarkably complex expression patterns during fly visual system development.…”
Section: Discussionsupporting
confidence: 76%
“…GPCRs are 7-transmembrane receptors that interact with many different stimuli including neurotransmitters and neuropeptides and play an important role in the physiology and function of neurons (Brody and Cravchik, 2000). More than 2/3 of the 124 GPCR genes encoded by the Drosophila genome are expressed in adult clock neurons, and these molecules alone can define clock neuron cell type (Schlichting et al, 2021). The data here indicate that these transcripts define equally well the DAN clusters (Figure 5A-B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Although the cycling of Dop1R1 mRNA levels is based only on RNA sequencing data, the bigger dopamine-mediated cAMP response from daytime than from nighttime brains suggests that Dop1R1 protein levels and activity in the two ITP + LNs are also higher in the daytime than the nighttime. This is the first indication that the cycling of GPCR mRNA levels 13,22,26 is of functional significance. Notably, the cycling of Dop1R1 RNA levels and protein/activity levels are likely not identical in the two neurons, a possibility that is supported by the larger sLNv day-night difference than LNd day-night difference in response to dopamine perfusion.…”
Section: Discussionmentioning
confidence: 80%
“…Although dopamine also enhances locomotor activity through its effect on lLNvs, 24 it has been reported to promote rather than inhibit sleep through its action on sLNvs and DN1s. 25,26 Despite these other results, it is hard to ignore the similar effects of neuronal inhibition and the Dop1R1 knockout; they both indicate that dopamine impacts the ITP + LNs to promote morning arousal. This period of time, between ZT00-ZT06, is not normally associated with evening cell activity.…”
Section: Discussionmentioning
confidence: 99%